A Chip Off the Old Block: Parents’ Subtle Ethnic Prejudice Predicts Children’s Implicit Prejudice - Pirchio, Sabine; Passiatore, Ylenia; Panno, Angelo; Maricchiolo, Fridanna; Carrus, Giuseppe (Frontiers in Psychology, 2018)
The increasing flow of immigrants in many European countries and the growing presence of children from immigrant families in schools makes it relevant to study the development of prejudice in children. Parents play an important role in shaping children’s values and their attitudes toward members of other ethnic groups; an intergenerational transmission of prejudice has been found in a number of studies targeting adolescents. The present study aims to investigate the intergenerational transmission of ethnic prejudice in 3- to 9- year-old children and its relations to parenting styles. Parents’ blatant and subtle ethnic prejudice and parenting style were measured together with children’s explicit and implicit ethnic prejudice in pupils and parents of preschool and primary schools in the region of Rome, Italy (N = 318). Results showed that parents’ subtle prejudice predicts children’s implicit prejudice regardless of the parenting style. Findings indicate that children might acquire prejudice by means of the parents’ implicit cognition and automatic behavior and educational actions. Implications for future studies and insights for possible applied interventions are discussed.